Use of expressed breast milk for pain relief during venepuncture in neonates - S., Abinaya; S., Vinoth; S., Ramesh (International Journal of Contemporary Pediatrics, 2018)
Background: It is now known that repeated pain in neonatal period influences neurodevelopmental outcome. It is necessary to assess and manage neonatal pain with appropriate interventions. The objective is to study whether expressed breast milk effectively reduces neonatal pain after venepuncture in comparison to placebo using sterile water. Methods: In this randomised controlled trial, neonates were randomised into two groups-expressed breast milk group and placebo group with 40 neonates in each group. Two minutes before venepuncture, 2 ml of test solution was administered. Mean Premature Infant Pain Profile (PIPP) score and mean cry time were recorded in neonates of both groups after venepuncture and compared. Results: At 0-30 second, 1-1 ½ minute, 3-3 ½ minute, 5-5 ½ minute after venepuncture, neonates in placebo group had mean PIPP score of 11.475, 10.125, 9.125, 7.575 respectively. At the same time intervals, mean PIPP score was 9.375, 7.825, 6.475, 5.05 in neonates of expressed breast milk group. Mean cry time after venepuncture was 105.65 seconds and 75.825 seconds in the placebo group and expressed breast milk group respectively. Conclusions: Compared to placebo, expressed breast milk significantly reduced mean PIPP score and cry time in neonates.